Youth identities and social trajectories in gated communities of Argentina. The case of Nordelta - Mutuverría, Marcos (Última Década, 2020)
The article analyses the identity construction of young people in Nordelta, from the study of their social trajectories, their lives in a gated community and the incidence of mobility in their daily socio-cultural practices. This new study converses to the youth-related research field, focusing on upper-middle class young people, particularly residents of Nordelta gated community, considered as a paradigm in the north zone of Buenos Aires Metropolitan Area, Argentina. Perceptions towards zigzagging trajectories, presence of stigmatizations, mobility analyses and time usage strategies in relation to long distances are shown.